Effect of different surface applications and adhesive systems on bond strength of porcelain repair material - (:unkn) unknown (Trans Tech Publications Ltd, 2012)
The purpose of this study was to evaluate the effect of different surface treatments and adhesive systems on bond strength of composite resin to porcelain when there is need to repair the restoration. Materials and methods: Rectangular discs (10mm × 12mm) with a height of 2mm were prepared from leucite-reinforced feldspathic ceramic CAD/CAM blocks (Vitablocs), embedded in acrylic resin, and bur cut porcelain surfaces were created. The specimens were divided into three groups (n=20) according to the surface treatments: Er:YAG laser at 2W for 20 seconds, air abrasion with 50μm AL2O 3 at 2.5 bar for 15 seconds, and the last group left untreated as control. After silane (Monobond S) application on ten specimens from each group, composite rods (Aelite Flo LV) with 4.25mm diameter and 4mm height were bonded to ceramic surfaces with a self-etch adhesive system (All-Bond SE). The remaining ten specimens from each group were etched with 36% orthophosphoric acid (Blue Etch Dental Etching Gel), and after silane and bonding agent (One-Step Plus) application composite rods with the mentioned dimensions were bonded. All groups were stored in distilled water at 37°C for one day before mechanical testing. Shear testing of all groups were performed on a universal testing machine with a load cell of 50kg and at a crosshead speed of 1.5mm/min. Results were statistically analyzed using Mann Whitney U and Kruskall Wallis tests. Results: The bond strength values of the self-etch adhesive system in the lased and control groups were statistically higher in comparison to the other adhesive system (p<0.01, p<0.05, respectively). The highest bond strength values were obtained in the Er:YAG lased and self-etch adhesive applied group. Conclusions: When there is need to repair of a porcelain restoration, a self-etch adhesive application after Er:YAG laser treatment could be the method of choice. © (2012) Trans Tech Publications.
Keywords: Adhesive system; Air abrasion; Composite; Laser; Porcelain repair